America becoming : racial trends and their consequences - Smelser, Neil J.; Wilson, William J., 1935-; Mitchell, Faith, 1952- (National Academy Press, 2001)
Publisher's description: Leading scholars and commentators explore past and current trends among African Americans, Hispanics, Asian Americans, and Native Americans in the context of a White majority. This collection of papers represents the most current literature in the field. Volume 1 covers demographic trends, immigration, racial attitudes, and the geography of opportunity. Volume 2 deals with the criminal justice system, the labor market, welfare, and health trends. Both books will be of great interest to educators, scholars, researchers, students, social scientists, and policymakers.